Chromogranin A and cortisol at intraoperative repeated noxious stimuli: Surgical stress in a dog model - Höglund, Odd Viking (SAGE Open Med, 2015)
OBJECTIVES: Biomarkers representing sympathetic tone and the surgical stress response are measured to objectively evaluate surgical techniques and anaesthetic protocols. If a part of the intraoperative procedure is repeated on the contralateral organ, one animal may potentially serve as its own control and, if so, may minimize the problem of individual differences of the stress response to anaesthesia and surgery. This study aimed to investigate the use of chromogranin A for measurement of the intraoperative sympathetic tone. Additional aims were to investigate chromogranin A and cortisol as indicators of the intraoperative surgical stress response caused by repeated noxious stimuli in dogs subjected to ovariohysterectomy and thereby to investigate the possibility of one dog serving as its own control. METHODS: Experiments were carried out on 10 dogs subjected to ovariohysterectomy. Perioperative blood samples (0–6) were collected after premedication, immediately before induction of anaesthesia (0), after induction of anaesthesia and before incision (1), before (2) and after (3) removal of the first ovary, after a 15-min pause before removal of the second ovary (4), after removal of the second ovary (5) and after closing the abdomen (6). Plasma chromogranin A and cortisol were analysed. RESULTS: Plasma chromogranin A did not change. Plasma cortisol concentration did not change between before anaesthesia and opening of the abdomen. Plasma cortisol increased at removal of the first ovary. Cortisol did not change at removal of the second ovary but remained increased compared to initial sample. CONCLUSION: The results suggest chromogranin A is a poor indicator of intraoperative sympathetic tone during elective surgery in dogs. Cortisol measurement was useful for assessment of intraoperative noxious stimuli. However, at these test conditions, neither plasma chromogranin A nor plasma cortisol was useful for assessment of repeated intraoperative noxious stimuli where one dog served as its own control.